Graphic Stylistic Means in the Epistolary Texts of Lesya Ukrainka (Linguostylistic Studies, 2020)
The article highlights the use of graphic stylistic means in the epistolary texts of Lesya Ukrainka, namely, the use of an underscore as paragraphemic stylistic device. The paragraphemic stylistic devices include syngraphemics (punctuation variation mechanism, when punctuation marks are put haphazardly in the sentence), supragraphemics (font variation mechanism), topographics (mechanism of varying the plane and space of the text). In the focus of the study are the most significant pragmatic functions of graphic stylistic means. They are: the function of attracting the attention of the addressee (these graphic stylistic means are used against the background of a graphically neutral text, and therefore the graphically unusually defined areas of the text attract attention; the function of emphasizing the elements which are communicatively most important (the information to be noticed by the addressee instantly); the function of clarification (logically-accentuating expression, when the new communicative information referred to in the sentence is emphasized); the function of compositional articulation of the text (graphic stylistic means facilitate the pragmatic orientation of the addressee in the process of perception of the literary text, separating the narrator’s plan and the character’s plan, real actions and fictional); the information compression function (graphic stylistic devices serve the purpose of language economy, when the punctuation marks, being so obvious in the text, are perceived as independent signals of evaluative content). Graphical stylistic means reveal the author’s attitude to what is written and are a means of expressing appreciation. The study has revealed that Lesya Ukrainka most often uses underlining in etiquette situations when she points to certain attributive features and quantitative characteristics, editorial corrections, names of cities, addresses, dates, or days of the week. In her letters, the most numerous group among the emphasized independent parts of speech are verbs.
Keywords: paragraphemics; syngraphemics; supragraphemics; topographems; emphasis